Pengaruh Kepemilikan Institusional, Profitabilitas dan Green Accounting Terhadap Nilai Perusahaan - Tiffany, Sheila Tiffany; Louis, Viana; Utama, Felicia; Nasution, Siti Aisyah; Anggono (Akuntansi Prima, 2025)
This study aims to determine the effect of institutional ownership, return on assets, return on equity, and green accounting on firm value in companies in the food and beverage industry listed on the Indonesia Stock Exchange. The selected research population was 25 food and beverage subsector companies for the 20202022 period, resulting in 75 research samples. The partial research results show that simultaneously, the variables of institutional ownership, return on assets, return on equity, and green accounting have a positive and significant effect on firm value. Partially, the variable of institutional ownership has a negative and significant effect on firm value, but the variables of return on assets, return on equity, and green accounting have no effect on firm value in food and beverage subsector companies listed on the Indonesia Stock Exchange for the 2020-2022 period.